Linguistic approximations of distances for indoor location authority - Olowolayemo, Akeem Koye; Md Tap, Abu Osman; Mantoro, Teddy (IEEE, 2014)
Positioning gadgets such as GPS devices often used for positioning references, navigation, and location updates in location aware applications, present outputs in coordinates and numerical forms, such as 20m from/to a point of interest or landmark. However, to human mind, the 20m is reprocessed into some linguistic variables such as almost there, close or far, etc. That is, human mind does not measure precisely or cannot 'reckon' the 20m in crisp measurement; it just imagines it and linguistically approximates such distances. Hence, the question is 'why can't the outputs from GPS and other such devices be provided in linguistic forms that are more appropriate and realistic to humans, while at the same time not enforcing unrealistic standards in the approximations. The aim of this study therefore is to provide fuzzy linguistic representation of distance approximations between a user and other entities. Entities in this regard will include facilities of interest and landmarks in location-aware system in indoor space. This work is an attempt to model the general ways of language references used by people to approximate distances in linguistic form suitable for indoor environment navigation